0623 Respiratory Profiling of Community-dwelling Individuals Many Years After Polio Infection. (27th May 2020) - Li, X; Wang, M; Wang, J; Sun, T; Sun, Y; Dong, X; Li, J; Zhao, L; Zhang, X; Lv, C; Strohl, K; Han, F
Abstract: Introduction: To determine the presence of respiratory impairment in community-living subjects with a history of poliomyelitis. Methods: In a study conducted from July 2013-January 2014, we used a national database to recruit individuals (212 males, 86 females) from north and south provinces in China with a known prior poliomyelitis infection >25 years previously. 298 subjects (96.8%) completed overnight oximetry to collect the number/hr of drops in oxygen saturation >4% (ODI4 ) and Epworth Sleepiness Scale (ESS); many completed a metabolic and lipid panel, arterial blood gas analysis, chest x-ray (CXR), spirometry and maximal voluntary ventilation (MVV). Some completed risk profiling for OSA. Results: Age was 47.8 ± 6.7 years (M±SD) and, when known, the age of infection was 2.3 ± 1.8 yrs. As defined by ODI4 ≥ 5/hr, the frequency of sleep-disordered breathing (SDB) was 37.2%; 9% (n = 27) had an ODI4 ≥15/hr. Those with vs. those without SDB differed by male gender (81% vs 65%, p = 0.004) and BMI (25.9 vs 23.0kg/m 2, p < 0.001). ESS was within the normal range, but was higher in those with 6.8 ± 5.0 vs. without 5.2 ± 4.0 (p < 0.01) SDB. Spirometry and MVV revealed no differences among groups. Scoliosis on the CXR was present 26.1% of those with and 14.4% of those without SDB. ODI4 correlated weakly with body mass index (r = 0.40). Glucose levels or hyperglycemia were not different. A triglyceride level > 1.7 mmol/L was present in 47.2% of those with and 21.3% of those without SDB (p < 0.001). Conclusion: Mild (28%) and to a smaller extent moderate-severe (9%) SDB is present many years after surviving poliomyelitis in infancy. In most, sleepiness is low but scoliosis is often present, and associations to hyperlipidemia and obesity are not reflected in fasting glucose levels. Support: no